2018
DOI: 10.4102/jamba.v10i1.651
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing local traditional authorities as a potential strategy to combat the vagaries of climate change in Zimbabwe

Abstract: While the devastating vagaries of climate change are ravaging communities the world over, especially in Africa, and Zimbabwe in particular, the role of traditional authorities is being overlooked. This paper argues for a relentless push towards the unimpeded involvement of local traditional authorities (LTAs) in the mobilisation of rural communities to adopt appropriate climate change adaptation practices in Zimbabwe. Given its complexity and uniqueness, external intervention through government and non-governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Most indigenous practices were considered to be compatible with the traditions, beliefs, and cultural values and norms of smallholder farmers as indicated [ 91 ]. The findings agree with [ 92 ] who found that smallholder farmers in Zimbabwe usually adopt practices that reflect their local beliefs, values, and local realities. Similarly, smallholder farmers in Botswana were reported to have refused to use scientific forecast information because it did not reflect their socio-cultural values and beliefs [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Most indigenous practices were considered to be compatible with the traditions, beliefs, and cultural values and norms of smallholder farmers as indicated [ 91 ]. The findings agree with [ 92 ] who found that smallholder farmers in Zimbabwe usually adopt practices that reflect their local beliefs, values, and local realities. Similarly, smallholder farmers in Botswana were reported to have refused to use scientific forecast information because it did not reflect their socio-cultural values and beliefs [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Instead, we conducted 31 face-toface interviews with Village Heads from 31 of the 33 villages in Mabale ward. Village Heads are considered traditional authorities with an intimate knowledge of local livelihood issues (Musarandega et al, 2018). They are also important local decision makers and can play a key role in the uptake of novel agricultural technologies (Musarandega et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Village Heads are considered traditional authorities with an intimate knowledge of local livelihood issues (Musarandega et al, 2018). They are also important local decision makers and can play a key role in the uptake of novel agricultural technologies (Musarandega et al, 2018). Prior to the interviews, the researcher identified himself and informed interviewees of the concept and aims of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Land tenure security strongly incentivizes farmers to invest in climate change adaptation [ 71 ]. Traditional leaders in Zimbabwe have been useful in the governance of people in rural communities and can play a supportive role in climate change adaptation by enforcing traditional strategies for combating the negative effects of climate change [ 72 ]. Local farmers’ cooperatives, academic institutions, the private sector and non-governmental organizations provide an opportunity to implement climate-smart agricultural technologies, which sustainably increase yields under climate change [ 73 ].…”
Section: Resultsmentioning
confidence: 99%